Pengaruh Latihan Lunges Terhadap Akurasi Shooting Dalam Keterampilan Futsal Pada Siswa SD - Mahendra, Reza Rizky; Safari, Indra; Ahmad Fauzi, Rizal (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This study aims to determine the effect of lunges training on futsal shooting accuracy in elementary school students and whether there is an increase after following the training program. The method used is a quasi-experiment with a "nonequivalent control group design." The population of this study was extracurricular futsal students at elementary schools in Cirebon, with a purposive sampling sample of 20 male students aged 10-12 years who have futsal skills. The pretest was conducted on the control and experimental groups using a target shooting accuracy test. The experimental group was given lunges training as a treatment, then ended with a posttest. The results showed that lunges training had a significant effect on increasing shooting accuracy, as evidenced by a t-test with a significance value of 0.000 (<0.05), which means there was a significant increase before and after treatment Keywords: Lunges, Shooting Accuracy, Futsal Skills